IMPLEMENTASI KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH DALAM MENINGKATKAN MUTU PEMBELAJARAN DI SMA NEGERI 2 BINJAI - Dina Haryati; Haryati, Dina; Hamdani, M. Rizqi Febri; Mardiati, Mardiati (Institut Agama Islam Negeri Palangka Raya, 2024)
This study aims to analyze the implementation of transformational leadership by the principal in improving learning quality at SMA Negeri 2 Binjai. The research is grounded in the understanding that the principal serves as an agent of change who fosters an innovative, collaborative, and quality-oriented learning culture. A descriptive qualitative approach was employed, using observation, in-depth interviews, and documentation as data collection techniques. The research subjects included the principal, teachers, and students as key informants. The findings reveal that the principal practices transformational leadership through four core dimensions: idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration. The principal acts as a moral role model committed to the school’s vision of quality improvement, encourages teachers to think creatively, and provides personal support for their professional growth. This leadership approach has positively influenced teacher participation, instructional innovation, and student learning motivation. The study concludes that transformational leadership significantly contributes to creating a conducive and quality-oriented learning environment. The implication suggests that school leadership practices should emphasize participatory and inspirational approaches, while it is recommended that principals continue to strengthen collaborative and innovative cultures to address the challenges of educational quality in the digital era.